Translational control of Human Epidermal Growth Factor Receptors, HER2 and HER4 in response to cellular stresses in breast cancer cells - Edwards, Arnelle (2023)
The human epidermal growth factors (EGFR and HER2-4) are tyrosine kinase cell surface receptors that play key roles in cell signalling, growth, and differentiation. However, HER2 and HER4 are commonly overexpressed in breast cancer contributing to breast cancer aggressiveness. Translational mechanisms such as internal ribosome entry sites (IRESs) and upstream opening reading frames (uORFs) can mediate translation of specific mRNA under cell stress conditions when global translation is inhibited. Cancer cells can be exposed to many cell stress conditions such as hypoxia and nutrient starvation, and such translational control mechanisms can contribute to overexpression of mRNAs. EGFR mRNA contains an IRES in the 5’ untranslated region (5’ UTR) that maintains expression of a firefly luciferase reporter in response to stress conditions such as hypoxia. However, it is not known if the 5’ UTRs of the other HER family members (HER 2-4) contain an IRES. Additionally, HER2 mRNA contains a repressive uORF in the 5’ UTR and a translational derepression element (TDE) in the 3’ UTR. However, it has not been investigated whether HER2 5’ UTR can mediate an increase in translation in response to glutamine or glucose starvation as seen for ATF4 and GCN4 mRNA.